Determinants of directors' remuneration in Singapore. - Koo, Beng Young. (2008)
The empirical relationship between directors’ remuneration and firm performance, firm size, number of subsidiaries, investment opportunity, ownership structure and board structure is analyzed for a sample of 300 Singaporean firms in the year 2000.